PERAN ARTIFICIAL INTELLIGENCE (AI) DALAM MENINGKATKAN KOLABORASI ANTAR SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) - Abdul Latif; Siti Murtiningsih (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
The development of Artificial Intelligence (AI) has had a broad impact on the world of education, including in the teaching of Islamic Religious Education (PAI). This article aims to analyze the role of AI in enhancing collaboration between students and its implications for pedagogical transformation in Islamic educational environments. This research uses a qualitative approach with a literature review method. Primary data sources were obtained from books, scientific journal articles, conference proceedings, and documents that directly discuss the integration of Artificial Intelligence (AI) in the learning process, particularly in the context of collaboration and religious education. Meanwhile, secondary data sources were obtained from various literature on technology ethics, as well as digital education policies relevant to the research theme. The collected data were analyzed using content analysis, through three main stages: data reduction, theme categorization, and interpretation of meaning. The results show that the application of AI in PAI can strengthen collaborative learning through project-based learning models, AI-supported discussion forums, AI-based peer review systems, and AI-assisted simulation and gamification. Through AI technology, students are able to access broader Islamic resources, develop critical thinking skills, and foster a collaborative attitude in understanding Islamic values ​​contextually. However, this study also identified ethical and structural challenges such as algorithmic bias, data privacy violations, and the digital access gap, which have the potential to hinder the equitable distribution of Islamic education. The implications of this research emphasize the importance of digital literacy for Islamic Religious Education teachers, ethical regulation of technology in Islamic educational institutions, and strengthening the role of AI as a learning tool that is not only innovative but also oriented towards religious and collaborative character development in the digital era.